(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2013)
This contribution tries to throw new light on the area of the “case a mare”, dug in the 50s, and more specifically the northern sector of the district, called sector A. The studied area includes 5 different rooms attributable on two different housing units: the rooms Aa, Ab and Ac belong to the first while rooms Ad and Ae belong to the second. The rooms are described first in their present state, and then the intervention of virtual reconstruction that was carried out is presented. The reconstructions provided here are based on the comparison between other units outside the site of Nora (Ostia and Pompei above all) and on direct archaeological evidence found in situ. Finally, a description of the software, called Rhynoceros, used for the reconstruction is provided, with particular attention to the materials which were used.